2019
DOI: 10.3758/s13420-019-00381-w
|View full text |Cite
|
Sign up to set email alerts
|

Relative reinforcer rates determine pigeons’ attention allocation when separately trained stimuli are presented together

Abstract: Previous research suggests that organisms allocate more attention to stimuli associated with higher reinforcer rates. This finding has been replicated several times when stimuli are trained together as compounds, but not in other procedures. Thus, the generality of the relation between relative reinforcer rates and divided attention is not well established. Therefore, we investigated whether relative reinforcer rates determine attention allocation when stimuli are trained separately and then encountered togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Alternatively, a more parsimonious explanation is that food deliveries affect behaviors implicated in performance. In MTS procedures, subjects may learn to orient toward the correct comparison (e.g., Davison, 2018;Gomes-Ng et al, 2019) or engage in other mediating behaviors that bridge the gap between sample and comparison stimuli (e.g., Blough, 1959;Urcuioli, 1984Urcuioli, , 1985Urcuioli & Honig, 1980;Weaver et al, 1999). For example, Urcuioli (1985) showed that comparison choice was controlled by differential behavior during the sample phase rather than by the identity of the sample, so disrupting sample-specific behaviors reduced matching performance.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a more parsimonious explanation is that food deliveries affect behaviors implicated in performance. In MTS procedures, subjects may learn to orient toward the correct comparison (e.g., Davison, 2018;Gomes-Ng et al, 2019) or engage in other mediating behaviors that bridge the gap between sample and comparison stimuli (e.g., Blough, 1959;Urcuioli, 1984Urcuioli, , 1985Urcuioli & Honig, 1980;Weaver et al, 1999). For example, Urcuioli (1985) showed that comparison choice was controlled by differential behavior during the sample phase rather than by the identity of the sample, so disrupting sample-specific behaviors reduced matching performance.…”
Section: Discussionmentioning
confidence: 99%
“…Like Shahan and Podlesnik, Davison and Elliffe found that as the probability of reinforcer deliveries for correct responses according to one dimension increased, so did the frequency of correct responses according to that dimension, whereas correct responses according to the other dimension decreased. Thus, these experiments demonstrate that divided control between compoundstimulus dimensions depends on relative reinforcer rates (see also Davison, 2018;Gomes-Ng et al, 2019a, 2019bPodlesnik et al, 2012;Shahan & Podlesnik, 2007, 2008. Davison and Elliffe (2010) likened the contingencies in their experiment to those in a "reinforcementfor-errors" procedure, in which some reinforcers are delivered after incorrect responses.…”
mentioning
confidence: 83%
“…Although these dimensions may differ in their discriminability-color is discriminable immediately, whereas alternation frequency is only discriminable across time-we presented the sample stimulus for at least 5 s and arranged maximally different alternation frequencies with the goal to enhance the discriminability of the alternation-frequency dimension. We have previously used these two stimulus dimensions in other studies of divided stimulus control (Cowie et al, 2020;Gomes-Ng et al, 2019a, 2019b, and previous research-including Davison and Elliffe (2010)-shows that pigeons can discriminate well between frequencies of keylight-color alternation (e.g., Cowie et al, 2020;Gomes-Ng et al, 2019a, 2019bKrägeloh & Davison, 2003;Roberts, 1997;Roberts et al, 2000;Roberts & Mitchell, 1994).…”
mentioning
confidence: 99%
“…The pigeons were housed in a colony room with a time-shifted environment (lights on at 12 a.m., off at 4 p.m.). All pigeons had previous experience in a symbolic DMTS procedure (Gomes-Ng, Elliffe, & Cowie, 2019), but never with the peak procedure.…”
Section: Methods Subjectsmentioning
confidence: 99%